KEPEMIMPINAN ORGANISATORIS SEBAGAI SHARING POWER DALAM MEWUJUDKAN KESEIMBANGAN HUBUNGAN ATASAN DAN BAWAHAN PADA MTsN 10 BIREUEN - Ilwan Ilwan; Mesiono Mesiono (PIONIR: JURNAL PENDIDIKAN, 2021)
Leadership in an organization is a leading activity carried out by a leader in carrying out the activities of the organization as a whole. Organizational leadership is intended to coordinate, empower and make decisions from various parts and existing organizational resources. The formulation of the problem in this article examines the steps for implementing organizational leadership as sharing power in realizing a balanced relationship between superiors and subordinates at MTsN 10 Bireuen. The results showed that organizational leadership as sharing power in realizing a balanced relationship between superiors and subordinates at MTsN 10 Bireuen was carried out with a normal mechanism that was persuasive legalistic, namely by delegating the leadership functions of the head of MTsN 10 Bireuen to several subordinates who were structurally assisted by the head of MTsN 10 Bireuen.